The use of fuel surcharge to fund transport investments in Syria - Noujoum, Osama (Latakia University Journal - Economic and Legal Sciences Series, 2013)
The increase in economic activities and the size of population is usually associated with more demand on transport sector activities. Furthermore, maintaining, upgrading and modernising transport in an economy would eventually lead to reduce logistic and production costs, and more competitively priced products. However, financing the costs of maintaining and expanding the transport sector is increasingly becoming problematic, particularly when fiscal resources are limited. Introducing surcharge on fuel prices has been proven as a reliable option to mobilise funds necessary to finance transport sector investment. However, fuel surcharges normally lead to price inflation as transport sector outputs are inputs for most economic activities. This paper looks at possible impacts of introducing a fuel surcharge on transport investment financing and price inflation in Syrian economy . Findings show that a considerable part of fiscal funds would be generated from the 10% fuel price surcharge with very little impact on price inflation . عادةً ما يترافق تزايد حجم الأنشطة الاقتصادية وعدد السكان بزيادة الطلب على أنشطة قطاع النقل. كما أنّ تحديث قطاع النقل ورفع سوية خدماته من شأنه أن يخفض التكاليف اللوجستية وتكاليف الانتاج مما يؤدي إلى أسعار تنافسية للمنتجات. لكن تمويل التكاليف اللازمة للمحافظة على سوية جيدة لأنشطة قطاع النقل وتوسيعها يصبح مشكلة مهمة خصوصاً في ظل ضعف موارد المالية العامة . بالتالي، تشير التجارب إلى ما يسمى (رسم استهلاك الوقود) للمساهمة في تأمين الموارد المالية اللازمة لتمويل استثمارات قطاع النقل هو خيار مجدٍ و يمكن الاعتماد عليه . لكن عادةً ما يؤدي فرض هذا الرسم إلى رفع مستوى تضخم الأسعار ، كون مخرجات قطاع النقل تدخل في معظم الأنشطة الاقتصادية. ندرس في هذه الورقة الآثار المحتملة لفرض رسم استهلاك الوقود على تمويل استثمارات قطاع النقل وعلى مستوى تضخم الأسعار في الاقتصاد السوري. حيث تبين النتائج أنّ فرض رسم استهلاك للوقود بنسبة 10%من أسعار الوقود سيؤدي إلى تأمين قسم مهم من الموارد المالية وسيكون أثره على مستوى الأسعار محدوداً .